Touch DNA collection – Performance of four different swabs. (November 2019) - Comte, Jennifer; Baechler, Simon; Gervaix, Joelle; Lock, Eric; Milon, Marie-Pierre; Delémont, Olivier; Castella, Vincent
Highlights: Collaboration between police units, a DNA laboratory, and an academic institute. Experiments undertaken in controlled and quasi-operational conditions. COPAN 4N6FLOQSwabs™ [Genetics] presented the best overall performance. DNA on COPAN 4N6FLOQSwabs™ [Crime scene] degraded at room temperature storage after 3 months. Abstract: A collaborative study conducted by three police forensic units, a DNA laboratory, and a forensic academic institute was undertaken in order to compare the performance of four different swabs in controlled and quasi-operational conditions. For this purpose, a reference swab (Prionics cardboard evidence collection kit) currently used within the police forensic units and 3 challenger swabs (COPAN 4N6FLOQSwabs™ (Genetics variety), Puritan FAB-MINI-AP and Sarstedt Forensic Swab) were used for collecting DNA traces from previously used items (referred as "touch DNA" in this article) including on 60 collars, 60 screwdrivers and 60 steering wheels obtained from volunteers. For each comparison, the surface considered was divided into two equal components; one was sampled with the reference swab and the other with one of the three challenger swabs. This lead to a total of 360 samples. Conclusions were consistent within the four operational partners. From a practical point of view, the COPAN 4N6FLOQSwabs™ (Genetics variety) was judged the most convenient to use. Furthermore, it allowed the recovery of significantly more DNA from collars (0.65 vs 0.13 ng/μL) and steering wheels (2.82 vs 1.77 ng/μL), and a similar amount of DNA from screwdrivers (0.032 vs 0.026 ng/μL) compared with the Prionics reference swab. The two other challenger swabs provided results that were not significantly different from the reference swab, except for the Puritan swab, whose performance was significantly lower for steering wheels (0.37 vs 0.58 ng/μL). As part of a conservation study, 50 μL of a blood dilution (1/4 with PBS) was deposited on a total of 105 COPAN (Genetics and Crime Scene varieties), Prionics and Sarstedt swabs. They were stored within a cupboard at room temperature. The integrity of the recovered DNA was evaluated with NGM SElect™ DNA profiles after different time-spans ranging from 1 day to 12 months by comparing the height difference of the peaks occurring at the shortest and longest loci, respectively. DNA seemed to remain stable, except when using the COPAN 4N6FLOQSwabs™ treated with an antimicrobial agent (Crime scene variety), which resulted in significant DNA degradation. Following these tests, the COPAN 4N6FLOQSwabs™ (Genetics variety), a model with a desiccant, was selected for further testing in fully operational conditions.